VEGETATIONAL, EDAPHIC, AND ECOLOGICAL ATTRIBUTES IN FOREST FORMATIONS IN THE CERRADO BIOME - Martins, Thalles Oliveira; Venturoli, Fábio; Siqueira, Karoline Nascimento; Silva-Neto, Carlos de Melo; Fonseca, Carolinne de Sousa; Calil, Francine Neves (Floresta, 2019)
The objective of this study was to verify the existence of variations in the composition and distribution of tree species due to the chemical characteristics of the soil in a Semi-deciduous seasonal forest and Cerradão. 40 plots of 400 m² were installed randomly in the area, 25 plots distributed in the semi-deciduous seasonal forest and 15 plots distributed in the cerradão. The biodiversity richness presented an amplitude of 84 species for the semi-deciduous seasonal forest and 73 species for the cerradão. A density 2227 ind.ha-1 for cerradão and 1699 ind.ha-1 for semi-deciduous seasonal forest was observed. Diagrams of species and edaphic variables by means of canonical correlation analysis (CCA) showed that semi-deciduous seasonal forest species correlated with a higher amount of nutrients (K+ and P-), base saturation (V%), saturation by aluminum (M%), cation exchange capacity at pH 7 ((CEC)T), and manganese. The cerradão species correlated with a higher amount of zinc (Zn2+), iron (Fe3+), and pH in H2O.